Political party caucuses and democracy: contradictio in terminis? - Napier, Clive J.; Labuschagne, Pieter (Faculty of Humanities, University of the Free State, 2017)
The concept of “caucus” has historically been imbedded within practical politics and in the disciplines of political science and history. In a general sense, a caucus (also referred to as a parliamentary party) aims to reach agreement between individuals on specific matters. In parliamentary politics and at all levels of government a caucus forms an essential structure in the functioning of a political party within a legislature, being an integral part of the strategic makeup of parties from central parliament down to the local level. The leadership of political parties organise their members into groups, but individual members may also organise themselves into groups which are generally known as caucuses. In the various caucuses, general strategy, policies and the candidates to be voted for, or to be elected into office are decided and agreed upon – this, to ensure that the party demonstrates solidarity within the respective legislatures and to the outside world. The secret manner in which a party caucus operates within a supposedly transparent democracy raises a number of concerns. The question is whether such secrecy and the insistence that all party members of a caucus – particularly in parliamentary political systems – toe the party line, infringes on the diversity of interests that elected members are supposed to represent? The purpose and values of democratic representation presuppose a direct line from the individual voter(s) to the representatives in a legislature. The caucus in effect inserts a space between individuals and their respective legislatures which may require that diverse interests be sacrificed for the sake of solidarity and a common strategy. The aims of the article are to make specific reference to the South African experience to ascertain whether a caucus undermines the democratic principle of representation and is in effect a contradictio in terminis.
Keywords: Caucus; Parliamentary party; Political parties; Politics; Representative democracy